Positive electrode material and preparation method thereof, positive plate and battery
By introducing T2 and O3 phases into the O2 phase lithium-rich manganese-based cathode material to form a composite phase, the crystal phase ratio and structure are optimized, solving the problems of low lithium-ion migration efficiency and voltage decay, improving the electrical performance of the material and reducing the preparation cost, thus promoting market application.
Patent Information
- Application Number
- CN202511137163.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-14
- Publication Date
- 2025-11-28
- Estimated Expiration
- 2045-08-14
AI Technical Summary
Existing O2-phase lithium-rich manganese-based cathode materials suffer from low lithium-ion migration efficiency, incomplete ion exchange leading to lithium-deficient states, low initial coulombic efficiency, severe voltage decay, and high manufacturing costs, thus failing to achieve market application.
By introducing T2 and O3 phases into the O2 phase lithium-rich manganese-based cathode material to form a composite phase, and combining it with doped metal elements to optimize the crystal phase ratio and structure, a composite phase lithium-rich manganese-based material with specific crystal plane peak intensity was prepared by using specific calcination and ion exchange processes.
It significantly improves the specific capacity, cycle stability and rate performance of the material, reduces the manufacturing cost, solves the voltage decay problem, and achieves higher battery performance.
Smart Images

Figure CN121035196A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of batteries, in particular to a positive electrode material, a preparation method thereof, a positive electrode sheet and a battery. BACKGROUND
[0002] With the rapid development of the power battery market, it is urgent to develop a system with higher energy density. Considering that the positive electrode material is the short board in the battery system, the lithium-rich manganese-based layered oxygen material, as the highest known specific capacity of the positive electrode material, is expected to help the battery field to achieve a breakthrough. However, the O3-type lithium-rich manganese-based material produced by the traditional sintering method faces many technical problems, including fast capacity decay, low first coulomb efficiency, poor rate performance, and low compaction density, which seriously hinders the market application of the material. The root cause of a series of problems lies in the inherent microstructure of the O3 phase. Firstly, the lattice oxygen in the high-pressure section participates in the redox reaction process highly uncontrollably, leading to irreversible structure. Secondly, the lithium ion migration rate in the lithium-rich manganese-based material system is extremely low, making it difficult to achieve efficient and rapid deintercalation.
[0003] In recent years, an O2-type lithium-rich manganese-based positive electrode material with a new type of layered stacking mode has been widely studied to solve the above problems. The prior art first mixes the precursor, lithium salt and sodium salt in a certain proportion, and then sintering a P2 phase sodium ion layered oxide as an intermediate in a high temperature and air atmosphere, and then replacing the sodium ions with lithium ions at a low temperature by ion exchange method to prepare the O2-type lithium-rich manganese-based positive electrode material. Compared with the O3-type lithium-rich manganese-based positive electrode material prepared by the conventional sintering method, the O2-type exhibits superior cycle stability and structural reversibility.
[0004] However, the existing O2 phase lithium-rich manganese-based material and its preparation technology have the following main problems: Due to the low migration efficiency of lithium ions in the lithium-rich manganese-based positive electrode material, the ion exchange process is not complete, resulting in lithium vacancies in the initial bulk phase, forming a lithium-deficient state, which causes the capacity of the positive electrode material to be unable to fully develop, and the need for lithium supplementation from the electrolyte or the negative electrode, which is manifested as a first coulomb efficiency exceeding 110% in half-cell testing. The lithium-deficient characteristics of the pure O2 phase lithium-rich manganese-based positive electrode material do not have a significant advantage over the modified O3 phase lithium-rich manganese-based positive electrode material in terms of actual discharge specific capacity. In addition, although the special layered stacking structure makes the structure have higher reversibility, the O2 phase lithium-rich manganese-based positive electrode material still has a serious voltage decay problem, which is particularly evident under high rate conditions.
[0005] The ion exchange step in the preparation of pure O2 phase depends on a large amount of lithium source and sodium ions in the P2 sodium intermediate phase for ion exchange. Due to the high price and large volume of these lithium sources, the preparation cost is increased, the efficiency is decreased, and this becomes a huge barrier to industrial application.
[0006] The existing O2 phase lithium-rich manganese-based positive electrode material has not formed market application and is still in the technical development stage due to its own defects and immature process. SUMMARY
[0007] To solve the problems of the pure O2 phase lithium-rich manganese-based positive electrode material in the prior art, the application provides a positive electrode material, a preparation method thereof, a positive electrode sheet and a battery.
[0008] In a first aspect, the application provides a positive electrode material, which comprises a lithium-rich manganese-based oxide, and the chemical formula of the lithium-rich manganese-based oxide is Li x-y T y (Mn a Ni b Co (1-a-b) ) 2-x O2; wherein, 1.0≤x≤1.2, 0≤y≤0.03, 0.6≤a≤0.75, 0.2≤b≤0.4, and T is a doped metal element. The composite phase of the lithium-rich manganese-based oxide comprises an O2 phase, a T2 phase and an O3 phase. The sum of the molar ratios of the O2 phase and the T2 phase in the composite phase is less than or equal to 85%. The molar ratio of the O3 phase is greater than or equal to 15%.
[0009] The positive electrode material has a discharge gram capacity of 276 mAh / g at an electrochemical window of 2.0-4.8 V and a rate of 0.1 C, the first coulombic efficiency is reduced to 105%, and the positive electrode material still has a discharge gram capacity of more than 250 mAh / g at a charge-discharge rate of 0.5 C and 1 C, and the capacity retention rate is more than 80% after 50 cycles.
[0010] In an embodiment of the application, the molar ratio of the O2 phase in the composite phase is 65%-85%, the molar ratio of the T2 phase in the composite phase is 0%-20%, and the molar ratio of the O3 phase in the composite phase is 15%-30%.
[0011] In an embodiment of the application, the lithium-rich manganese-based oxide with the T2 phase structure has a characteristic peak corresponding to a (002) crystal face in the range of 17.4°≤θ1≤17.8°. The lithium-rich manganese-based oxide with the O2 phase structure has a characteristic peak corresponding to a (002) crystal face in the range of 18.2°≤θ2≤18.5°. The lithium-rich manganese-based oxide with the O3 phase structure has a characteristic peak corresponding to a (003) crystal face in the range of 18.5°≤θ3≤18.8°.
[0012] In an embodiment of the present application, the lithium-rich manganese-based oxide of the T2 phase structure has a characteristic peak intensity I1 of the (002) crystal face in the range of 17.4°≤θ1≤17.8°; The lithium-rich manganese-based oxide of the O2 phase structure has a characteristic peak intensity I2 of the (002) crystal face in the range of 18.2°≤θ2≤18.5°; The lithium-rich manganese-based oxide of the O3 phase structure has a characteristic peak intensity I3 of the (003) crystal face in the range of 18.5°≤θ3≤18.8°; The I1, I2, I3 satisfy 0<I1 / I2≤0.5, 0<I3 / I2≤0.5.
[0013] In an embodiment of the present application, the I1, I2, I3 satisfy 0≤I1 / I2≤0.2, 0.1≤I3 / I2≤0.3.
[0014] In an embodiment of the present application, the doped metal element is one or more of Ti, Zr, Mo, La and Nb.
[0015] In an embodiment of the present application, the lithium-rich manganese-based oxide is a single-crystal particle; Preferably, the particle size D50 of the lithium-rich manganese-based oxide is 1-5 μm; Preferably, the specific surface area of the lithium-rich manganese-based oxide is 1-35 m 2 / g.
[0016] In a second aspect, the present application provides a preparation method of a positive electrode material, comprising the following steps: mixing and calcining a sodium source, a first lithium source, a doped metal source and a precursor in a certain proportion to obtain a composite product containing single-crystal P2 phase sodium ion oxide and O3 phase lithium ion oxide; mixing the composite product with a second lithium source in a certain proportion and performing an ion exchange reaction to obtain a composite-phase lithium-rich manganese-based oxide; Preferably, the particle size D50 of the precursor is 2-8 μm; Preferably, the specific surface area of the precursor is 20-35 m 2 / g; Preferably, the calcination is performed at a temperature increasing rate of 1-10 ℃ / min; Preferably, the temperature of the calcination is 700-900 ℃, and the time of the calcination is 8-24 h; Preferably, the temperature increasing rate of the ion exchange reaction is 1-20 ℃ / min; Preferably, the ion exchange reaction is performed at one or more temperatures in the temperature range of 250-350 ℃; and the time of the ion exchange reaction is 4-15 h.
[0017] In a third aspect, the present application provides a positive electrode sheet, which comprises the positive electrode material as described above, or which comprises the positive electrode material prepared by the preparation method as described above.
[0018] In a fourth aspect, the present application provides a battery, which comprises the positive electrode material as described above, or which comprises the positive electrode sheet as described above.
[0019] Other features and advantages of the present application will be set forth in the description that follows, and in part will become apparent to those skilled in the art upon examination of the following or can be learned by practice of the present application. The objects and other advantages of the present application can be realized and attained by the structure particularly pointed out in the description and claims hereof as well as in the appended drawings. BRIEF DESCRIPTION OF DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following will briefly introduce the drawings needed to be used in the embodiments or prior art description. Obviously, the drawings described in the following description are some embodiments of the present application, and for those skilled in the art, other drawings can also be obtained from these drawings without any creative effort. In the following description, the positional relationship described in the drawings is the direction of the components drawn in the drawings as the reference, unless otherwise specified.
[0021] Figure 1 XRD pattern of the T2 / O2 / O3 composite phase lithium-rich manganese-based oxide prepared in Example 1 of the present application; Figure 2 XRD pattern of the O2 / O3 composite phase lithium-rich manganese-based oxide prepared in Example 2 of the present application; Figure 3 XRD pattern of the T2 / O2 composite phase lithium-rich manganese-based oxide prepared in Comparative Example 1 of the present application; Figure 4 XRD pattern of the T2 / O3 composite phase lithium-rich manganese-based oxide prepared in Comparative Example 2 of the present application; Figure 5 First circle charge-discharge curve of the button cell made of the positive electrode material in Example 1 of the present application; Figure 6 First circle charge-discharge curve of the button cell made of the positive electrode material in Example 2 of the present application; Figure 7 First circle charge-discharge curve of the button cell made of the positive electrode material in Example 3 of the present application; Figure 8 First circle charge-discharge curve of the button cell made of the positive electrode material in Example 4 of the present application; Figure 9The first circle charge-discharge curve of the button cell made of the positive electrode material of Example 5 of the present application; Figure 10 The first circle charge-discharge curve of the button cell made of the positive electrode material of Comparative Example 1 of the present application; Figure 11 The first circle charge-discharge curve of the button cell made of the positive electrode material of Comparative Example 2 of the present application; Figure 12 The first circle charge-discharge curve of the button cell made of the positive electrode material of Comparative Example 3 of the present application; Figure 13 The first circle charge-discharge curve of the button cell made of the positive electrode material of Comparative Example 4 of the present application; Figure 14 The comparison chart of the 50 circle cycle performance of the button cell made of the positive electrode material of the present application and Example 5 at 0.5C rate. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the embodiments of the present application will be described clearly and completely below in combination with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments of the present application; as long as the technical features designed in the different embodiments of the present application do not conflict with each other, they can be combined with each other; based on the embodiments in the present application, all other embodiments obtained by the person of ordinary skill in the art without making creative labor belong to the protection scope of the present application.
[0023] In the description of the present application, it should be noted that all the terms (including technical terms and scientific terms) used in the present application have the same meaning as that generally understood by the person of ordinary skill in the art to which the present application belongs, and should not be understood as a limitation on the present application; it should be further understood that the terms used in the present application should be understood as having the same meaning as the terms in the context of the present specification and the related field, and should not be understood in an idealized or overly formal sense, except as explicitly defined in the present application.
[0024] The present application introduces and controls T2 and O3 phases to prepare a composite phase in the O2 phase lithium-rich manganese-based positive electrode material, utilizes the physicochemical characteristics of each phase to establish a three-phase synergistic effect, and cooperates with single crystalization and bulk phase doping design, not only effectively solves the problems of voltage decay and lithium deficiency existing in the existing O2 phase lithium-rich manganese-based positive electrode material, but also greatly improves the specific capacity and rate performance of the positive electrode material, significantly improves the electrical performance of the positive electrode material; at the same time, the technical scheme has low cost and is easy to realize preparation, and is expected to accelerate the market application of the positive electrode material.
[0025] An embodiment of the present application provides a positive electrode material, which comprises a lithium-rich manganese-based oxide, and the chemical formula of the lithium-rich manganese-based oxide is Li x-y T y (Mn a Ni b Co (1-a-b) ) 2-x O2; wherein, 1.0≤x≤1.2, 0≤y≤0.03, 0.6≤a≤0.75, 0.2≤b≤0.4, and T is a doped metal element; The composite phase of the lithium-rich manganese-based oxide comprises O2 phase, T2 phase and O3 phase; The sum of the mole proportions of the O2 phase and the T2 phase in the composite phase is less than or equal to 85%, preferably 60%-80%, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, etc., but is not limited to the listed values, and other values not listed in the range are also applicable; the mole proportion of the O3 phase is greater than or equal to 15%, for example, 15%, 20%, 25%, 30% or any value therebetween.
[0026] It is worth noting that although other positive electrode material systems also have T2, O2 and O3 phases, the chemical composition, microstructure, role played and performance in the charge and discharge process of these phases in the lithium-rich manganese-based positive electrode material are completely different from those in other systems, which are described in detail as follows: O3 phase lithium-rich manganese-based oxides belong to stable state, have high specific capacity and lithium content, but its structure has poor reversibility in the charging and discharging process, and the interface side reaction is violent, resulting in a series of problems such as rapid capacity attenuation, low first coulomb efficiency and the like. O2 phase lithium-rich manganese-based oxides belong to metastable state, due to its special oxygen atom stacking structure, so that its structure is more stable, and in the charging and discharging process, the irreversible oxygen loss and transition metal ion migration can be inhibited, thus having high capacity and high cycle retention rate. However, the O2 phase depends on the ion exchange method for preparation, so there is a problem of body phase lithium deficiency, and in addition, the O2 phase still has the problem of voltage decay, which is particularly serious at high rate. The T2 phase lithium-rich manganese-based oxide belongs to a metastable orthorhombic phase, which is usually in a lithium-deficient state, and exhibits extremely high cycle stability in the charging and discharging process, but its capacity is low, so it is rarely considered in practical applications. The inventors have found that by introducing a certain amount of T2 phase and O3 phase into the O2 phase, not only the defects of O2, T2 and O3 phases can be compensated, but also a synergistic effect can be induced, so that the battery performance of the positive electrode material is greatly improved. The specific experiments show that the introduction of T2 phase into the O2 phase can improve the cycle performance of the material, and can improve the cycle stability and rate performance of the composite phase, but if the content of T2 phase is too high, the capacity of the material will decrease; the introduced O3 phase can form a solid solution with the O2 phase, optimize the cycle, and supplement lithium for the O2 phase in the charging and discharging process, solve the problem of lithium deficiency, and improve the capacity and cycle performance of the material, but if the proportion of O3 phase is too high, the cycle performance of the material will decrease and the impedance will increase sharply. In summary, in the lithium-rich manganese-based positive electrode material, the three phases are in a specific molar ratio range, which can form an effective synergistic effect, and significantly improve the overall performance of the positive electrode material.
[0027] In a preferred embodiment of the present application, the molar ratio of the O2 phase in the composite phase is 65%-85%, preferably 65%-75%, such as 65%, 70%, 75%, 80%, 85% or any value therebetween; the molar ratio of the T2 phase in the composite phase is 0%-20%, preferably 0%-15%, such as 0%, 5%, 10%, 15%, 20% or any value therebetween; and the molar ratio of the O3 phase in the composite phase is 15%-30%, preferably 20%-30%, such as 15%, 20%, 25%, 30% or any value therebetween.
[0028] In an embodiment of the present application, please refer to Figure 1 The lithium-rich manganese-based oxide with T2 phase structure has a characteristic peak corresponding to the (002) crystal face in the range of 17.4°≤θ1≤17.8°, wherein the lithium-rich manganese-based oxide with T2 phase structure has a characteristic peak intensity I1 corresponding to the (002) crystal face in the range of 17.4°≤θ1≤17.8°; The lithium-rich manganese-based oxide of the O2 phase structure has a characteristic peak corresponding to a (002) crystal face in the range of 18.2°≤θ2≤18.5°, wherein the lithium-rich manganese-based oxide of the O2 phase structure has a characteristic peak intensity I2 of the (002) crystal face in the range of 18.2°≤θ2≤18.5°; The lithium-rich manganese-based oxide of the O3 phase structure has a characteristic peak corresponding to a (003) crystal face in the range of 18.5°≤θ3≤18.8°, wherein the lithium-rich manganese-based oxide of the O3 phase structure has a characteristic peak intensity I3 of the (003) crystal face in the range of 18.5°≤θ3≤18.8°.
[0029] In a preferred embodiment of the present application, the I1, I2 and I3 satisfy 0
[0030] In an embodiment of the present application, the doped metal element is one or more of Ti, Zr, Mo, La and Nb. In the composite-phase lithium-rich manganese-based oxide of the present application, transition metal element T is doped, which aims to: (1) the selected doped element ions serve to support the layered structure and widen the lithium ion transmission channel, which can improve the ion exchange efficiency; (2) the selected doped element is enriched at the near-surface of the crystal grain, which serves to inhibit oxygen evolution and protect the interface, which can effectively reduce the interface side reaction and improve the reversibility of the oxygen anion redox, thereby improving the capacity and cycle retention rate of the positive electrode material; (3) the selected doped element can control the grain growth during sintering and ion exchange, refine the grain, and improve the particle morphology, further improving the capacity and compaction density of the positive electrode material.
[0031] In a preferred embodiment of the present application, the lithium-rich manganese-based oxide is a single-crystal particle; the particle size D50 of the lithium-rich manganese-based oxide is 1-5 μm, for example 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or any value therebetween; the specific surface area of the lithium-rich manganese-based oxide is 1 m 2 / g-35 m 2 / g, for example 1 m 2 / g, 2 m 2 / g, 3 m 2 / g, 4 m 2 / g, 5 m 2 / g, 6 m 2 / g, 7 m 2 / g, 8 m 2 / g, 9 m 2 / g, 10 m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g or any value therebetween. By using single crystal particles with small particle size, not only the lithium ion migration efficiency can be improved, but also the surface of all particles can be fully in contact with the electrolyte, further improving the electrical performance of the positive electrode material.
[0032] The application provides a preparation method of a positive electrode material, comprising the following steps: Step one, mix and calcine a sodium source, a first lithium source, a doped metal source and a precursor in proportion to obtain a composite product containing single crystal P2 phase sodium ion oxide and O3 phase lithium ion oxide; In an example embodiment of the application, the sodium source, the first lithium source, the doped metal source and the precursor are preferably mixed in a molar ratio of n(Na):n(Li):n(T):n(Mn+Ni+Co) = 0.83:(x-y-1):y:(2-x) and calcined to obtain the composite product containing single crystal P2 phase sodium ion oxide and O3 phase lithium ion oxide; it should be noted that the doped metal source can be selected to be added or not added according to actual conditions.
[0033] In an example embodiment of the application, in the step one, the sodium source is sodium carbonate or sodium hydroxide; the first lithium source is lithium carbonate or lithium hydroxide; and the doped metal source is one or more of titanium oxide, zirconium oxide, lanthanum oxide, molybdenum oxalate and niobium oxalate.
[0034] In an example embodiment of the application, in the precursor, the binary precursor is a nickel-manganese hydroxide or carbonate compound, and n(Ni):n(Mn)=a:b; the ternary precursor is a nickel-cobalt-manganese hydroxide or carbonate compound, and n(Ni):n(Mn):n(Co)=a:b:(1-a-b); preferably, the particle size D50 of the precursor is 2-8 μm, such as 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm or any value therebetween; and the specific surface area of the precursor is 20-35 m 2 / g, such as 20 m 2 / g, 21m 2 / g, 22m 2 / g, 23m 2 / g, 24m 2 / g, 25m 2 / g, 26m 2 / g, 27m 2 / g, 28m 2 / g, 29m 2 / g, 30m 2 / g, 31m 2 / g, 32m 2 / g, 33m 2 / g, 34m 2 / g, 35m 2 / g, or any value therebetween; by obtaining a composite product with smaller particle size and larger specific surface area, the ion conversion efficiency is improved.
[0035] In an exemplary embodiment of the present application, the calcination is performed at a temperature increasing rate of 1-10°C / min, such as 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or any value therebetween; the temperature of the calcination is 700-900°C, such as 700°C, 750°C, 800°C, 850°C, 900°C, or any value therebetween; the time of the calcination is 8-24h, such as 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, or any value therebetween.
[0036] Step two, mixing the composite product with a second lithium source in a certain proportion and performing ion exchange reaction to obtain a composite-phase lithium-rich manganese-based oxide; In an exemplary embodiment of the present application, the composite product obtained in step one is mixed with a second lithium source in a certain proportion, and then ion exchange is performed at low temperature, residual salt is removed by water washing, and finally composite-phase lithium-rich manganese-based oxide powder is obtained by vacuum drying. In an exemplary embodiment of the present application, in step two, the second lithium source is lithium nitrate or a mixture of lithium nitrate and lithium chloride, and the exchange process replaces sodium ions and part of vacancies in the composite product with lithium ions to form T2 and O2 phases.
[0037] In an exemplary embodiment of the present application, the temperature increasing rate of the ion exchange reaction is 1-20°C / min, such as 2°C / min, 4°C / min, 6°C / min, 8°C / min, 10°C / min, 12°C / min, 14°C / min, 16°C / min, 18°C / min, 20°C / min, or any value therebetween.
[0038] In an exemplary embodiment of the present application, the ion exchange reaction is carried out at one or more temperatures in the range of 250-350°C, such as 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, or any value therebetween; and the ion exchange reaction is carried out for a time period of 4-15h, such as 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, or any value therebetween.
[0039] In another exemplary embodiment of the present application, the ion exchange reaction is carried out at one or more temperatures in the range of 250-350°C. Preferably, the temperature is preferably above 250°C and below 320°C, such as 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, or any value therebetween.
[0040] It is worth noting that different exchange temperatures can create suitable conditions for each phase formation at different stages, and the low temperature range is conducive to the formation of metastable O2 phase; and the ion exchange reaction can be more complete as the temperature increases, further improving the degree of ion exchange and the lithium content of the system.
[0041] The mixing ratio of the composite product and the second lithium source in step two is preferably 1-5, such as 1, 2, 3, 4, 5, or any value therebetween, for example. By adjusting the exchange temperature and the lithium-sodium ion ratio, the ratio of T2 phase and O2 phase can be adjusted. In addition, using less second lithium source can also reduce the cost of the ion exchange step, increase the loading amount and thus improve the yield.
[0042] In addition, the positive electrode sheet and the battery of the present application are described below.
[0043] Generally, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the charging and discharging process of the battery, active ions are embedded and extracted between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0044] The positive electrode sheet includes a positive electrode current collector and a positive electrode material layer arranged on at least one surface of the positive electrode current collector, and the positive electrode material layer includes the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the method of the second aspect of the present application.
[0045] As a non-limiting example, the positive current collector has two surfaces opposite in the thickness direction thereof, and the positive active material layer is provided on either or both of the two surfaces of the positive current collector.
[0046] In some embodiments of the present application, the positive current collector can be a metal foil or a composite current collector.
[0047] The negative electrode sheet includes a negative current collector and a negative active material layer provided on at least one surface of the negative current collector, the negative active material layer including a negative active material.
[0048] As a non-limiting example, the negative current collector has two surfaces opposite in the thickness direction thereof, and the negative active material layer is provided on either or both of the two surfaces of the negative current collector.
[0049] In some embodiments of the present application, the negative current collector can be a metal foil or a composite current collector.
[0050] In some embodiments of the present application, the negative active material can be any known in the art for use in a battery.
[0051] The electrolyte has a function of conducting ions between the positive electrode sheet and the negative electrode sheet. The present application does not have a particular limitation on the type of electrolyte, which can be selected as desired. For example, the electrolyte can be in a liquid state, a gel state, or a solid state.
[0052] In some embodiments of the present application, the battery further includes a separator. The present application does not have a particular limitation on the type of separator, which can be any known porous separator having good chemical stability and mechanical stability.
[0053] In some embodiments of the present application, the battery can include one or more battery cells. In the present application, the "battery cell" refers to a basic unit capable of converting chemical energy and electrical energy to each other, and further generally includes at least a positive electrode sheet, a negative electrode sheet, and an electrolyte, unless otherwise specified. During charging and discharging of the battery, active ions are inserted into and extracted from the positive electrode sheet and the negative electrode sheet. The electrolyte has a function of conducting the active ions between the positive electrode sheet and the negative electrode sheet.
[0054] The present application does not have a particular limitation on the shape of the battery cell, which can be cylindrical, square, or any other shape.
[0055] In the present application, the battery can also be a battery module or a battery pack.
[0056] The battery module includes at least one battery cell. The number of battery cells included in the battery module can be one or more, and a person skilled in the art can select an appropriate number according to the application and capacity of the battery module.
[0057] Hereinafter, an embodiment of the present application will be described. The following examples are illustrative, and are not intended to limit the present application. In the examples, unless otherwise noted, techniques or conditions are performed according to those described in the literature or according to the product manual. In the examples, unless otherwise noted, the reagents or instruments are commercially available products.
[0058] Example 1 The present embodiment provides a preparation method of a T2 / O2 / O3 composite phase lithium-rich manganese-based positive electrode material, comprising the following steps: Step one, sodium carbonate, lithium carbonate and nickel-manganese binary hydroxide (n(Ni):n(Mn)=0.25:0.75) are uniformly mixed according to the ratio of n(Na):n(Li):n(Mn+Ni)=0.83:0.25:0.75 to obtain a mixed powder sample. The mixed powder sample is sent into a box furnace, first raised to 450℃ at a rate of 3℃ / min and kept for 5h, then raised to 800℃ at a rate of 3℃ / min and kept for 12h, and then cooled to room temperature with the furnace to obtain a composite product of P2 phase sodium ion oxide and O3 phase lithium ion oxide.
[0059] Step two, the composite product obtained in step one is uniformly mixed with lithium nitrate according to the ratio of n(Na):n(Li)=1:3 to obtain a mixed powder sample. The mixed powder sample is sent into a low-temperature furnace for static ion exchange, raised to 280℃ at a rate of 10℃ / min and kept for 4h, and then cooled to room temperature with the furnace. After crushing, water washing and drying, a composite phase lithium-rich manganese-based oxide powder is obtained.
[0060] Example 2 The present embodiment provides a preparation method of a T2 / O2 / O3 composite phase lithium-rich manganese-based positive electrode material, comprising the following steps: Step one, sodium carbonate, lithium carbonate and nickel-cobalt-manganese ternary hydroxide (n(Ni):n(Co):n(Mn)=0.2:0.1:0.7) are uniformly mixed according to the ratio of n(Na):n(Li):n(Mn+Ni+Co)=0.83:0.25:0.75 to obtain a mixed powder sample. The mixed powder sample is sent into a box furnace, first raised to 450℃ at a rate of 3℃ / min and kept for 5h, then raised to 900℃ at a rate of 3℃ / min and kept for 12h, and then cooled to room temperature with the furnace to obtain a composite product of P2 phase sodium ion oxide and O3 phase lithium ion oxide.
[0061] Step two, the composite product obtained in step one is uniformly mixed with lithium nitrate according to the ratio of n(Na):n(Li)=1:3 to obtain a mixed powder sample. The mixed powder sample is sent into a low-temperature furnace for static ion exchange, first heated to 280℃ at a rate of 10℃ / min for 2h, then heated to 320℃ at a rate of 1℃ / min for 6h, and then cooled to room temperature with the furnace. After crushing, water washing and drying, a composite phase lithium-rich manganese-based oxide powder is obtained.
[0062] Example 3 The embodiment provides a preparation method of a T2 / O2 / O3 composite phase lithium-rich manganese-based positive electrode material, which comprises the following steps: Step one, sodium carbonate, lithium carbonate, ammonium niobium oxalate and nickel-manganese binary hydroxide (n(Ni):n(Mn)=0.25:0.75) are uniformly mixed according to the ratio of n(Na):n(Li):n(Nb)):n(Mn+Ni)=0.83:0.23:0.02:0.75 to obtain a mixed powder sample. The mixed powder sample is sent into a box-type furnace, first heated to 450℃ at a rate of 3℃ / min for 5h, then heated to 800℃ at a rate of 3℃ / min for 12h, and then cooled to room temperature with the furnace. A composite product of P2 phase sodium ion oxide and O3 phase lithium ion oxide is obtained.
[0063] Step two, the composite product obtained in step one is uniformly mixed with lithium nitrate according to the ratio of n(Na):n(Li)=1:3 to obtain a mixed powder sample. The mixed powder sample is sent into a low-temperature furnace for static ion exchange, first heated to 280℃ at a rate of 10℃ / min for 2h, then heated to 320℃ at a rate of 1℃ / min for 6h, and then cooled to room temperature with the furnace. After crushing, water washing and drying, a composite phase lithium-rich manganese-based oxide powder is obtained.
[0064] Example 4 The embodiment provides a preparation method of a T2 / O2 / O3 composite phase lithium-rich manganese-based positive electrode material, which comprises the following steps: Step one, sodium carbonate, lithium carbonate, ammonium niobium oxalate and nickel-manganese binary hydroxide (n(Ni):n(Mn)=0.25:0.75) are uniformly mixed according to the ratio of n(Na):n(Li):n(Nb)):n(Mn+Ni)=0.83:0.23:0.02:0.75 to obtain a mixed powder sample. The mixed powder sample is sent into a box-type furnace, first heated to 450℃ at a rate of 3℃ / min for 5h, then heated to 800℃ at a rate of 3℃ / min for 12h, and then cooled to room temperature with the furnace. A composite product of P2 phase sodium ion oxide and O3 phase lithium ion oxide is obtained.
[0065] Step two, the composite product obtained in step one is uniformly mixed with lithium nitrate according to the ratio of n(Na):n(Li)=1:3 to obtain a mixed powder sample. The mixed powder sample is sent into a low-temperature furnace for static ion exchange, heated to 280℃ at a rate of 10℃ / min for 4h, and then cooled to room temperature with the furnace. After crushing, water washing and drying, a composite phase lithium-rich manganese-based oxide powder is obtained.
[0066] Example 5 The embodiment provides a preparation method of a T2 / O2 / O3 composite phase lithium-rich manganese-based positive electrode material, which comprises the following steps: Step one, sodium carbonate, lithium carbonate, ammonium niobium oxalate and nickel-manganese binary hydroxide (n(Ni):n(Mn)=0.25:0.75) are uniformly mixed according to the ratio of n(Na):n(Li):n(Nb):n(Mn+Ni)=0.83:0.23:0.02:0.75 to obtain a mixed powder sample. The mixed powder sample is sent into a box-type furnace, first heated to 450℃ at a rate of 3℃ / min for 5h, then heated to 850℃ at a rate of 3℃ / min for 12h, and then cooled to room temperature with the furnace to obtain a composite product of P2 phase sodium ion oxide and O3 phase lithium ion oxide.
[0067] Step two, the composite product obtained in step one is uniformly mixed with lithium nitrate according to the ratio of n(Na):n(Li)=1:3 to obtain a mixed powder sample. The mixed powder sample is sent into a low-temperature furnace for static ion exchange, heated to 280℃ at a rate of 10℃ / min for 4h, and then cooled to room temperature with the furnace. After crushing, water washing and drying, a composite phase lithium-rich manganese-based oxide powder is obtained.
[0068] Comparative Example 1 The comparative example provides a preparation method of a T2 / O2 composite phase lithium-rich manganese-based positive electrode material, which comprises the following steps: Step one, sodium carbonate, lithium carbonate, ammonium niobium oxalate and nickel-manganese binary hydroxide (n(Ni):n(Mn)=0.25:0.75) are uniformly mixed according to the ratio of n(Na):n(Li):n(Nb):n(Mn+Ni)=0.83:0.08:0.02:0.9 to obtain a mixed powder sample. The mixed powder sample is sent into a box-type furnace, first heated to 450℃ at a rate of 3℃ / min for 5h, then heated to 850℃ at a rate of 3℃ / min for 12h, and then cooled to room temperature with the furnace to obtain a P2 phase sodium ion oxide.
[0069] Step two, the composite product obtained in step one is uniformly mixed with lithium nitrate according to the ratio of n(Na):n(Li)=1:3 to obtain a mixed powder sample. The mixed powder sample is sent into a low-temperature furnace for static ion exchange, heated to 280℃ at a rate of 10℃ / min for 4h, and then cooled to room temperature with the furnace. After crushing, water washing and drying, a composite phase lithium-rich manganese-based oxide powder is obtained.
[0070] Comparative Example 2 The present comparative example provides a preparation method of a T2 / O3 composite phase lithium-rich manganese-based positive electrode material, comprising the following steps: Step one, sodium carbonate, lithium carbonate, ammonium niobium oxalate and nickel-manganese binary hydroxide (n(Ni):n(Mn)=0.25:0.75) are uniformly mixed according to the ratio of n(Na):n(Li):n(Nb):n(Mn+Ni)=0.83:0.23:0.02:0.75 to obtain a mixed powder sample. The mixed powder sample is sent into a box-type furnace, first heated to 450℃ at a rate of 3℃ / min for 5h, and then heated to 800℃ at a rate of 3℃ / min for 12h, and then cooled to room temperature with the furnace to obtain a composite product of P2 phase sodium ion oxide and O3 phase lithium ion oxide.
[0071] Step two, the composite product obtained in step one is uniformly mixed with lithium nitrate according to the ratio of n(Na):n(Li)=1:3 to obtain a mixed powder sample. The mixed powder sample is sent into a low-temperature furnace for static ion exchange, first heated to 280℃ at a rate of 10℃ / min for 2h, and then heated to 380℃ at a rate of 1℃ / min for 6h, and then cooled to room temperature with the furnace. After crushing, water washing and drying, a composite phase lithium-rich manganese-based oxide powder is obtained.
[0072] Comparative Example 3 The present comparative example provides a preparation method of a T2 / O2 / O3 composite phase lithium-rich manganese-based positive electrode material, comprising the following steps: Step one, sodium carbonate, lithium carbonate, ammonium niobium oxalate and nickel-manganese binary hydroxide (n(Ni):n(Mn)=0.25:0.75) are uniformly mixed according to the ratio of n(Na):n(Li):n(Nb):n(Mn+Ni)=0.83:0.33:0.02:0.65 to obtain a mixed powder sample. The mixed powder sample is sent into a box-type furnace, first heated to 450℃ at a rate of 3℃ / min for 5h, and then heated to 800℃ at a rate of 3℃ / min for 12h, and then cooled to room temperature with the furnace to obtain a composite product of P2 phase sodium ion oxide and O3 phase lithium ion oxide.
[0073] Step two, the composite product obtained in step one was uniformly mixed with lithium nitrate according to the ratio of n(Na):n(Li)=1:3 to obtain a mixed powder sample. The mixed powder sample was sent into a low-temperature furnace for static ion exchange, first heated to 280℃ at a rate of 10℃ / min for 2h, then heated to 350℃ at a rate of 1℃ / min for 6h, and then cooled to room temperature with the furnace. After crushing, water washing and drying, a composite phase lithium-rich manganese-based oxide powder was obtained.
[0074] Comparative Example 4 The present comparative example provides a preparation method of a T2 / O2 / O3 composite phase lithium-rich manganese-based positive electrode material, comprising the following steps: Step one, sodium carbonate, lithium carbonate, ammonium niobium oxalate and nickel-manganese binary hydroxide (n(Ni):n(Mn)=0.25:0.75) were uniformly mixed according to the ratio of n(Na):n(Li):n(Nb):n(Mn+Ni)=0.83:0.13:0.02:0.85 to obtain a mixed powder sample. The mixed powder sample was sent into a box-type furnace, first heated to 450℃ at a rate of 3℃ / min for 5h, then heated to 850℃ at a rate of 3℃ / min for 12h, and then cooled to room temperature with the furnace to obtain a composite product of P2 phase sodium ion oxide and O3 phase lithium ion oxide.
[0075] Step two, the composite product obtained in step one was uniformly mixed with lithium nitrate according to the ratio of n(Na):n(Li)=1:3 to obtain a mixed powder sample. The mixed powder sample was sent into a low-temperature furnace for static ion exchange, first heated to 280℃ at a rate of 10℃ / min for 2h, then heated to 310℃ at a rate of 1℃ / min for 6h, and then cooled to room temperature with the furnace. After crushing, water washing and drying, a composite phase lithium-rich manganese-based oxide powder was obtained.
[0076] Battery preparation The positive electrode materials obtained in each example and comparative example were used to prepare lithium ion battery positive electrode sheets, respectively: The positive electrode material, conductive additive Super P and binder polyvinylidene fluoride were mixed according to a mass ratio of 90:5:5, and an appropriate amount of organic solvent N-methyl pyrrolidone was added to form a uniformly dispersed slurry. The slurry was uniformly coated on an aluminum foil current collector by means of a doctor blade, and then placed in an oven for drying at 130℃ for 20 min. The dried aluminum foil was rolled and cut into circular electrode sheets, which were stored in a vacuum oven at 80℃ for 12h. The dried positive electrode sheets, separators, electrolyte and negative electrode sheets were sequentially assembled in a glove box to prepare lithium ion batteries.
[0077] Bulk characterization Figure 1 XRD pattern of the T2 / O2 / O3 composite phase lithium-rich manganese-based oxide prepared in Example 1; Figure 2 XRD pattern of the O2 / O3 composite phase lithium-rich manganese-based oxide prepared in Example 2; Figure 3 XRD pattern of the T2 / O2 composite phase lithium-rich manganese-based oxide prepared in Comparative Example 1; Figure 4 XRD pattern of the T2 / O3 composite phase lithium-rich manganese-based oxide prepared in Comparative Example 2; From Figure 1 It can be seen that the lithium-rich manganese-based oxide of the T2 phase structure has a characteristic peak corresponding to the (002) crystal face in the range of 17.4°≤θ1≤17.8°; the lithium-rich manganese-based oxide of the O2 phase structure has a characteristic peak corresponding to the (002) crystal face in the range of 18.2°≤θ2≤18.5°; and the lithium-rich manganese-based oxide of the O3 phase structure has a characteristic peak corresponding to the (003) crystal face in the range of 18.5°≤θ3≤18.8°.
[0078] The positive electrode materials prepared in the above Examples 1-5 and Comparative Examples 1-4 were subjected to XRD diffraction characterization, and the phase composition therein was calculated, wherein Table 1 is the molar ratio of each phase of the positive electrode materials in each example and comparative example obtained by XRD test.
[0079] Table 1
[0080] Electrochemical performance testing Specific capacity and first coulombic efficiency test: at room temperature, 0.1C constant current charging to 4.8V, then constant voltage charging, the cutoff current is 0.02C, then discharging to 2.0V with 0.1C constant current, record the discharge specific capacity and the first coulombic efficiency.
[0081] Rate performance test: at room temperature, the first cycle is activated first, 0.5C and 1C constant current charging to 4.8V, then constant voltage charging, the cutoff current is 0.02C, then discharging to 2.0V with 0.1C constant current, record the discharge capacity, repeat the above steps 50 times, record the discharge capacity of the first cycle C1 and the capacity of the 50th cycle C50, the capacity retention rate of 50 cycles %=(C50 / C1)*100%.
[0082] The test results are shown in the following table.
[0083] Table 2
[0084] According to the above table, reference is made to Figure 5 and Figure 14mAh / g, 220 mAh / g, the initial coulombic efficiency at 0.1C is 110%, the capacity retention rates at 0.5C and 1C for 50 cycles are 92% and 84%, respectively; Reference Figure 6 mAh / g, 245 mAh / g, the initial coulombic efficiency at 0.1C is 109%, the capacity retention rates at 0.5C and 1C for 50 cycles are 80% and 81%, respectively.
[0085] Reference Figure 7 mAh / g, 252 mAh / g, the initial coulombic efficiency at 0.1C is 100%, the capacity retention rates at 0.5C and 1C for 50 cycles are 89% and 83%, respectively.
[0086] Reference Figure 8 and Figure 14 mAh / g, 251 mAh / g, the initial coulombic efficiency at 0.1C is 106%, the capacity retention rates at 0.5C and 1C for 50 cycles are 89% and 81%, respectively.
[0087] Reference Figure 9 and Figure 14 mAh / g, 244 mAh / g, the initial coulombic efficiency at 0.1C is 105%, the capacity retention rates at 0.5C and 1C for 50 cycles are 85% and 83%, respectively.
[0088] Reference Figure 10 and Figure 14The discharge specific capacity of the button cell made of the positive electrode material of Comparative Example 1 at 0.1C, 0.5C and 1C rates was 246 mAh / g, 251 mAh / g and 244 mAh / g, respectively, the initial coulombic efficiency at 0.1C was 127%, and the capacity retention rate after 50 cycles at 0.5C and 1C was 84% and 81%, respectively. Due to the lack of O3 phase, the positive electrode material was seriously deficient in lithium, the initial coulombic efficiency was too high, and it was difficult to apply to full cells in actual production; at the same time, the synergistic effect was destroyed, the capacity and cycle performance were also deteriorated, and the performance was significantly worse than that of the examples.
[0089] Reference Figure 11 and Figure 14 The discharge specific capacity of the button cell made of the positive electrode material of Comparative Example 2 at 0.1C, 0.5C and 1C rates was 203 mAh / g, 190 mAh / g and 185 mAh / g, respectively, the initial coulombic efficiency at 0.1C was 92%, and the capacity retention rate after 50 cycles at 0.5C and 1C was 105% and 99%, respectively. Due to the lack of O2 phase, the capacity at all rates was greatly reduced, the O3 structure collapsed rapidly during charging, forming a stable spinel phase and a rock salt phase, and no longer exhibiting the lithium-rich characteristics, and the performance was significantly worse than that of the examples.
[0090] Reference Figure 12 and Figure 14 The discharge specific capacity of the button cell made of the positive electrode material of Comparative Example 3 at 0.1C, 0.5C and 1C rates was 243 mAh / g, 239 mAh / g and 234 mAh / g, respectively, the initial coulombic efficiency at 0.1C was 112%, and the capacity retention rate after 50 cycles at 0.5C and 1C was 88% and 86%, respectively. Due to the molar ratio of T2, O2 and O3 phases not being within the control range of the present application, the synergistic effect was poor, the capacity at all rates was decreased, the initial coulombic efficiency was increased, and the performance was significantly worse than that of the examples.
[0091] Reference Figure 13 and Figure 14 The discharge specific capacity of the button cell made of the positive electrode material of Comparative Example 4 at 0.1C, 0.5C and 1C rates was 251 mAh / g, 245 mAh / g and 233 mAh / g, respectively, the initial coulombic efficiency at 0.1C was 116%, and the capacity retention rate after 50 cycles at 0.5C and 1C was 85% and 82%, respectively. In Comparative Example 4, the ratio of T2 and O2 phases was within the constraint range of claim 1, but the ratio of T2+O2 phases exceeded 85%, so the synergistic effect was poor, the capacity at all rates was decreased, the initial coulombic efficiency was increased, and the performance was significantly worse than that of the examples.
[0092] In summary, compared with the prior art, the composite phase lithium-rich manganese-based positive electrode material prepared by the application has the advantages that by introducing T2 and O3 phases into O2 phase lithium-rich manganese-based positive electrode material and regulating the proportion of the T2 and O3 phases to obtain a synergistic effect, and by using the complex phase doping technology, the specific capacity, cycle retention rate and rate performance of the composite phase lithium-rich manganese-based positive electrode material are significantly improved.
[0093] In addition, those skilled in the art should understand that, although there are many problems in the prior art, each embodiment or technical solution of the application can only be improved in one or several aspects, and it is not necessary to solve all the technical problems listed in the prior art or background art at the same time. Those skilled in the art should understand that what is not mentioned in a claim should not be regarded as a limitation of the claim.
[0094] Although terms such as positive electrode material, lithium-rich manganese-based oxide, composite phase, nanometer source, lithium source, doping metal source, precursor, ion exchange reaction, etc. are used more frequently in this document, the possibility of using other terms is not excluded. The use of these terms is only to facilitate the description and explanation of the essence of the application; any additional limitation by interpreting them is contrary to the spirit of the application; the terms "first", "second", etc. (if any) in the specification and claims of the embodiments of the application and the above-described drawings are used to distinguish similar objects, and do not necessarily describe a specific order or sequence.
[0095] Finally, it should be pointed out that: the above embodiments are only used to illustrate the technical solutions of the application, and not to limit them; although the application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the foregoing embodiments, or make equivalent replacement for part or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solution deviate from the scope of the technical solutions of the embodiments of the application.
Claims
1. A positive electrode material, characterized in that, The cathode material includes a lithium-rich manganese-based oxide, the chemical formula of which is Li. x-y T y (Mn a Ni b Co (1-a-b) ) 2-x O2; where 1.0≤x≤1.2, 0≤y≤0.03, 0.6≤a≤0.75, 0.2≤b≤0.4, and T is the doped metal element; The composite phase of the lithium-rich manganese-based oxide includes an O2 phase, a T2 phase, and an O3 phase; Wherein, the sum of the molar proportions of the O2 phase and the T2 phase in the composite phase is less than or equal to 85%; The molar proportion of the O3 phase is greater than or equal to 15%.
2. The cathode material according to claim 1, characterized in that, The molar proportion of the O2 phase in the composite phase is 65%-85%, the molar proportion of the T2 phase in the composite phase is 0%-20%, and the molar proportion of the O3 phase in the composite phase is 15%-30%.
3. The cathode material according to claim 1, characterized in that, The lithium-rich manganese-based oxide with the T2 phase structure has characteristic peaks corresponding to the (002) crystal plane in the range of 17.4°≤θ1≤17.8°; The lithium-rich manganese-based oxide with the O2 phase structure has characteristic peaks corresponding to the (002) crystal plane in the range of 18.2°≤θ2≤18.5°; The lithium-rich manganese-based oxide with the O3 phase structure has characteristic peaks for the (003) crystal plane in the range of 18.5°≤θ3≤18.8°.
4. The cathode material according to claim 3, characterized in that, The lithium-rich manganese-based oxide with the T2 phase structure has a characteristic peak intensity of I1 corresponding to the (002) crystal plane in the range of 17.4°≤θ1≤17.8°; The lithium-rich manganese-based oxide with the O2 phase structure has a characteristic peak intensity of I2 on the (002) crystal plane in the range of 18.2°≤θ2≤18.5°. The lithium-rich manganese-based oxide with the O3 phase structure has a characteristic peak intensity of I3 on the (003) crystal plane in the range of 18.5°≤θ3≤18.8°. The I1, I2, and I3 satisfy 0 < I1 / I2 ≤ 0.5 and 0 < I3 / I2 ≤ 0.
5.
5. The positive electrode material according to claim 4, characterized in that, The I1, I2, and I3 satisfy 0 ≤ I1 / I2 ≤ 0.2 and 0.1 ≤ I3 / I2 ≤ 0.
3.
6. The cathode material according to claim 4, characterized in that, The doped metal element is one or more of Ti, Zr, Mo, La and Nb.
7. The cathode material according to claim 1, characterized in that, The lithium-rich manganese-based oxide is a single crystal particle; Preferably, the particle size D50 of the lithium-rich manganese-based oxide is 1-5 μm; Preferably, the specific surface area of the lithium-rich manganese-based oxide is 1-35 m². 2 / g.
8. A method for preparing a positive electrode material, characterized in that, Includes the following steps: Sodium source, first lithium source, doped metal source and precursor are mixed and calcined in proportion to obtain a composite product containing single crystal P2 phase sodium ion oxide and O3 phase lithium ion oxide. The composite product was mixed with a second lithium source in a certain proportion and subjected to an ion exchange reaction to obtain a composite phase lithium-rich manganese-based oxide. Preferably, the particle size D50 of the precursor is 2-8 μm; Preferably, the specific surface area of the precursor is 20-35 m². 2 / g; Preferably, the calcination is carried out at a heating rate of 1-10℃ / min; Preferably, the calcination temperature is 700-900℃; the calcination time is 8-24 hours. Preferably, the heating rate of the ion exchange reaction is 1-20 °C / min; Preferably, the ion exchange reaction is carried out at one or more temperatures within the temperature range of 250-350°C; the duration of the ion exchange reaction is 4-15 hours.
9. A positive electrode sheet, wherein the positive electrode sheet comprises the positive electrode material according to any one of claims 1-7, or the positive electrode sheet comprises the positive electrode material prepared by the preparation method according to claim 8.
10. A battery, characterized in that, The battery comprises the positive electrode material according to any one of claims 1-7, or the battery comprises the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Metastable-phase lithium-rich manganese-based positive electrode material, preparation method thereof and lithium ion battery
CN116443940A
O2-type lithium-rich manganese-based positive electrode material and preparation and application thereof
CN117996067A
Lithium-rich manganese-based oxide, preparation method, positive electrode material and battery
CN119029198A
Preferred orientation single crystal lithium-rich manganese-based positive electrode material, preparation method thereof and lithium ion battery
CN119786590A
High-voltage ternary positive electrode material with core-shell structure and preparation method therefor
WO2023130779A1